Compassion – an imperative for nursing education and practice - Luís Condeço (Millenium)
Historically grounded in ethical, religious, and philosophical values, compassion is understood as a sensitive response to the suffering of others, accompanied by a genuine intention to alleviate it. Florence Nightingale, a founding reference of modern nursing, already considered it an indispensable attribute, capable of giving meaning to care and dignity to the patient (Straughair, 2012).